Do audited firms have better access to credit?: Evidence from emerging countries - Yaqoub Alduraywish (Cogent Business & Management, 2023)
This study aims to examine the relationship of having financial statements audited by external auditors and access to bank credit, using data from the Business Environment and Enterprise Performance Survey (BEEPS). Among firms having credit access, this research further analyses the impacts of auditing financial statements on loan value, loan rate, and loan term (duration) by applying the Heckman two-step models with sample selection. Results show that firms with audited financial statements have better formal credit access than their counterparts. Among these, audited firms obtain bigger loan value, have lower loan rates and shorter borrowing duration, as compared to non-audited firms. Results are robust when applying the Propensity Score Matching.
Keywords: C21; G21; M42; 650; audit; credit access; financial statements; firm and country levels